Physical education of future woman-officers of the state border service for formation of readiness to physical self-development at academy education as a pedagogical problem - Sliusarchuk, V.; Iedynak, G. (Journal of Education, Health and Sport, 2015)
The article analyses the information of documentary materials and scientific literature related to the state of development of problem of physical education of female students studying in higher military educational institutions of the State Border Guard Service. There is established the availability of some data about peculiarities of physical education of future military female officers. One of the main conclusions of such studies is the need for differentiation of the content of physical education on the basis of sex. According to this, we note lack of research aimed at development of effective approaches for formation and implementation of content of physical education for female students who study in institutions of higher education of the State Border Guard Service. Implementation of such innovations will enhance the effectiveness of educational process for formation readiness of future female officers to carry out professional activities.